Enhancing time-stamping techniqe by implementing media access control address [electronic resource] - Pacu Putra Suarli, 1989- (2013)
Thesis (Sarjana Sains Komputer (Keselamatan Maklumat))) - Universiti Teknologi Malaysia, 2013